2007
DOI: 10.1136/ard.2006.054098
|View full text |Cite
|
Sign up to set email alerts
|

No efficacy of subcutaneous methotrexate in active ankylosing spondylitis: a 16-week open-label trial

Abstract: Objective: To examine the potential therapeutic effect of methotrexate 20 mg given weekly as subcutaneous injections to 20 patients with ankylosing spondylitis refractory to nonsteriodal antirheumatic drugs. Patients and methods: 20 patients with ankylosing spondylitis, a mean Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score of 5.6 (range 4-9.3) and predominantly axial manifestations were treated with weekly 15 mg methotrexate subcutaneously for 4 weeks, which was then increased to 20 mg subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(103 citation statements)
references
References 14 publications
1
89
1
10
Order By: Relevance
“…The patients with axial disease seem to respond readily to anti-tumor necrosis factor (TNF) medications, a phenomenon also seen repeatedly in the adult literature [15•]. Several studies have shown a lack of efficacy for DMARDs in axial disease [16][17][18]. Additionally, there is evidence in the adult literature that while symptoms can be well controlled by anti-TNF agents, radiographic progression may be difficult to halt once initiated [14,19,20].…”
Section: Axial Versus Peripheral Disease In Eramentioning
confidence: 92%
“…The patients with axial disease seem to respond readily to anti-tumor necrosis factor (TNF) medications, a phenomenon also seen repeatedly in the adult literature [15•]. Several studies have shown a lack of efficacy for DMARDs in axial disease [16][17][18]. Additionally, there is evidence in the adult literature that while symptoms can be well controlled by anti-TNF agents, radiographic progression may be difficult to halt once initiated [14,19,20].…”
Section: Axial Versus Peripheral Disease In Eramentioning
confidence: 92%
“…The ASAS criteria have been developed as classification criteria but they are likely be useful as diagnostic criteria, especially in patients with non-radiographic axial SpA at an outpatient rheumatology clinic (van den Berg & van der Heijde, 2010). This may help to make an early diagnosis and prevent the current diagnostic delay, described as 5 to 10 years between the first occurrence of symptoms and an AS diagnosis (Feldtkeller et al, 2003;Haibel et al, 2007). It prevents unnecessary diagnostic tests and more importantly makes it possible to commence more effective therapies earlier.…”
Section: Biomarkers For Early Diagnostic Purposesmentioning
confidence: 99%
“…Gonzalez-Lopez et al, reported significant improvement with MTX in physical well-being, BASDAI, BASFI, physician and patient global assessments, the HAQ, and spinal pain [14]. Haibel et al studied the role of subcutaneous MTX at doses of 20 mg/week for 16 weeks in a NSAID refractory AS patients with axial symptoms and found ASAS 20, 50 and 70 responses of 25%, 10% and none respectively, with no change in BASDAI [11]. In a recent Cochrane review, it was concluded that MTX may not improve overall disease activity, physical function, overall pain, tenderness or swelling in the ligaments of the joints, movement of the spine, stiffness and overall well-being [15].…”
Section: Introductionmentioning
confidence: 99%
“…Though MTX monotherapy has not been found to be effective in axial symptoms of SpA in a number of studies, it has been reported to be useful in patients with peripheral arthritis [9][10][11][12][13]. Gonzalez-Lopez et al, reported significant improvement with MTX in physical well-being, BASDAI, BASFI, physician and patient global assessments, the HAQ, and spinal pain [14].…”
Section: Introductionmentioning
confidence: 99%